Development and investigation of common wheat lines of winter cultivar Bezostaya 1 with combinations of dominant alleles of VRN-1 loci - E. V. Chumanova; T. T. Efremova; Y. V. Kruchinina; L. A. Pershina (Вавиловский журнал генетики и селекции, 2019)
VRN genes, determining wheat sensitivity to vernalization, are the main genetic system that defnes the duration of the entire growing period and the durations of the main organogenesis phases. To date, several alleles have been described for VRN-1 loci, and allelespecifc primers have been developed that allow rapid identifcation of allelic spectra in common wheat varieties and lines. The unequal inﬂuence of diﬀerent alleles of VRN-1 loci on the duration of the growing period has also been shown; however, there is little information on the eﬀect of the combination of diﬀerent alleles on heading time. In developing genotypes having diﬀerent alleles of dominant VRN genes on the base of the same genetic background, it is necessary to study the genetic eﬀects of VRN genes on the duration of the growing season and the individual developmental phases, as well as on productivity. Most varieties presently grown in Russia carry the dominant alleles of two VRN-1 genes: Vrn-A1a and Vrn-B1a or Vrn-B1c; thus, the task was to create lines combining the dominant alleles of Vrn-A1a with Vrn-B1a and Vrn-B1c against the genetic background of the winter variety Bezostaya 1 (Bez1 Vrn-A1a/Vrn-B1a and Bez1 Vrn-A1a/Vrn-B1c). Homozygous plants were isolated in the F2 generation by using known allelespecifc primers for the Vrn-A1 and Vrn-B1 loci. The durations of the tillering–frst node period, which is the key stage determining growing duration, and the period from shoots to heading were signifcantly reduced in lines with a combination of two dominant alleles of VRN-1 loci compared to isogenic lines of Bezostaya 1 with the dominant alleles Vrn-B1a and Vrn-B1c. The duration of these developmental phases also decreased in the obtained lines as compared to the isogenic line containing the dominant Vrn-A1a allele, but the diﬀerences were not signifcant. No substantial diﬀerences were found in the duration of other growing phases in lines with two dominant alleles of the VRN-1 loci as compared to isogenic lines of Bezostaya 1.